2002
DOI: 10.1037/h0095005
|View full text |Cite
|
Sign up to set email alerts
|

Perceived stigma and community integration among clients of assertive community treatment.

Abstract: Facilitating the integration of persons with psychiatric disabilities is an important goal of community programs. In addition to limitations such as inadequate housing, poverty, and unemployment, a common barrier to community adjustment identified by people with psychiatric disabilities is their perception of being stigmatized. This study examined the relationships between perceived stigma and community integration in 95 clients of assertive community treatment (ACT) teams, using sequential multiple regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
94
1
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(107 citation statements)
references
References 47 publications
11
94
1
1
Order By: Relevance
“…Not all areas of community life are adequately covered by the established EBPs. Social integration, involving reciprocal relationships between consumers and others in society, has not been adequately achieved (Angell, 2003;Prince & Prince, 2002). Certainly, more work also is needed in the areas of jail diversion, treatment for medical conditions, and treatment for trauma and co-occurring post-traumatic stress disorder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Not all areas of community life are adequately covered by the established EBPs. Social integration, involving reciprocal relationships between consumers and others in society, has not been adequately achieved (Angell, 2003;Prince & Prince, 2002). Certainly, more work also is needed in the areas of jail diversion, treatment for medical conditions, and treatment for trauma and co-occurring post-traumatic stress disorder.…”
Section: Discussionmentioning
confidence: 99%
“…In their contacts with mental health centers, consumers often experience ''spirit-breaking'' messages reflecting low expectations regarding their potential to realize their dreams (Prince & Prince, 2002). Mirroring prejudices of the general community, many practitioners believe that independent living is beyond the ability of many consumers.…”
Section: Stigmatizing Attitudesmentioning
confidence: 99%
“…Autrement, la stigmatisation peut faire obstacle à l'intégra-tion sociale, interférer avec la performance des rôles sociaux, réduire les attentes de vie et diminuer la qualité de vie. Les conséquences de la stigmatisation -manque de travail, absence de logement, faible estime de soi et peu de soutien social -peuvent être des obstacles majeurs au rétablissement, avoir un impact sur le pronostic à long terme, et pousser à l'incapacité (Link et al, 1991 ;Markowitz, 1998 ;Wahl, 1999 ;Prince et Prince, 2002). La stigmatisation peut aussi produire de graves bouleversements dans les relations familiales et, en raison d'un désir de secret, réduire les interactions sociales normales (Wahl et Harman, 1989).…”
Section: Conséquences De La Stigmatisationunclassified
“…Yanos et al (2007) found little association between community participation and type of neighbourhood (degree of stability of residence, concentration of immigrants, level of economic disadvantage), though Segal, Baumohl and Moyles (1980) found greater degrees of acceptance associated with liberal, non-traditional and working class neighbourhoods. Perceptions of community would also seem important as demonstrated by Prince and Prince (2002), who found that higher levels of perceived stigma were associated with lower community activity levels, and by Kloos and Townley (2011), who found that the perceptions of a better neighbourhood social climate has an inverse relationship with psychological distress.…”
Section: Factors Associated With Community Participationmentioning
confidence: 99%